Stress Management as The Main Strategy in Improving Teachers' Work Effectiveness - Fitriyanti, Evi; Retnowati, Rita; Suhardi, Eka (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The high workload of teachers causes stress and has an impact on their work effectiveness, and it is hoped that through stress management, teachers can increase their work effectiveness. This study aims to explore the influence of stress management on the work effectiveness of civil servant teachers in State Elementary Schools. The method used was quantitative, using SEM-PLS and SITOREM analysis. Data was collected through the distribution of questionnaires to 163 teachers who were randomly selected from 47 schools. The results of the study showed that the influence of stress management on teachers' work effectiveness was very small. This influence is not very significant in the model. with a track coefficient value of 0.058, T-statistic 1.308, and P-value 0.191. SITOREM analysis shows that the main indicators of teachers' work effectiveness are teaching motivation and teaching readiness, while in stress management, time management, and a healthy lifestyle are the top priorities. This study shows that although stress management has a theoretical contribution in supporting teachers' work, this factor is not the main determinant of teachers' work effectiveness. Educational organizations must focus more on improving professional competence, teaching motivation, and creating a conducive work environment, while still paying attention to the importance of stress management as an element that supports teachers' work effectiveness. Further research is suggested to explore the relationship between psychological, professional, and environmental factors in more depth, as well as involve qualitative methods to gain more comprehensive insights related to teachers' work dynamics.